The role of tourism development in boosting export product diversification in China: A provincial perspective - Ul-Haq, Jabbar; Khanum, Sana; Oad, Salochina; Hye, Qazi Muhammad Adnan; Khan, Zahid Ullah (Journal of Tourism Management Research, 2023)
Tourism has emerged as a major sector, and it is considered a significant contributor to the development of the host countries. Tourism development (TD) is believed, inter alia, to be a key promoter of export product diversification (EPD). This study explores the liaison between tourism development and export product diversification in China and across its regions (i.e., Eastern, Central, & Western) using the data for the period of 2011-2019. The Driscoll-Kraay standard errors (DKSEs) is adopted for empirical analysis along with feasible generalized least-squares (FGLS) and panel-corrected standard errors (PCSEs). The findings revealed an inverted U-shaped liaison between the TD and EPD. The estimates are robust and insensitive to econometric models, measures of tourism development, and the inclusion of other key covariates. The relationship between industrial structure, natural resource endowments, human capital, and economic growth is positive and statistically significant. The study revealed similar findings that were significant across regions. The policy insinuation is that the government should devise such policies to boost TD in order to promote EPD and sustainable development.